Cover Image. (2nd June 2019) - Niu, Yujie; Zhu, Huimin; Yang, Siwei; Ma, Sujie; Zhou, Jianwei; Chu, Bin; Hua, Rui; Hua, Limin
Abstract : The cover image is based on the Research Article Overgrazing leads to soil cracking that later triggers the severe degradation of alpine meadows on the Tibetan Plateau by Yujie Niu et al., http://doi.org/10.1002/ldr.3312